Предмет: Алгебра, автор: taniachaika61

решите уравнение
(2-x sqrt{6} ) sqrt{2} =2(x- sqrt{6})

Ответы

Автор ответа: Firuza25
0
(2-x sqrt{6}) sqrt{2}  = 2(x- sqrt{6}
2 sqrt{2} -x sqrt{12} =2x-2 sqrt{6}
2 sqrt{2} -2x sqrt{3} =2x-2 sqrt{6}
2x sqrt{3}+2x=2 sqrt{6}+2 sqrt{2}
2x( sqrt{3}+1)=2( sqrt{6}+ sqrt{2})
x( sqrt{3}+1)=( sqrt{6}  + sqrt{2} )
x= frac{ sqrt{6}+ sqrt{2}}{ sqrt{3}+1} = frac{( sqrt{6}+ sqrt{2})( sqrt{3}-1)}{( sqrt{3}+1)( sqrt{3}-1)} = frac{ sqrt{18}- sqrt{6}+ sqrt{6}- sqrt{2}}{3-1}= frac{ sqrt{18}-  sqrt{2}}{2}=  frac{3 sqrt{2}- sqrt{2}}{2}=  \ = frac{2 sqrt{2}}{2}= sqrt{2}
Похожие вопросы
Предмет: Геометрия, автор: barbossa9292